2020
DOI: 10.1016/j.omtn.2020.02.007
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: lncRNA PVT1/MicroRNA-17-5p/PTEN Axis Regulates Secretion of E2 and P4, Proliferation, and Apoptosis of Ovarian Granulosa Cells in PCOS

Abstract: Recently, the roles of microRNAs (miRNAs) and long non-coding RNAs (lncRNAs) were identified in polycystic ovary syndrome (PCOS). In the present study, we investigated the role of the lncRNA PVT1/miR-17-5p/PTEN axis in PCOS ovarian granulosa cells. Expression of PVT1, miR-17-5p and PTEN in PCOS ovarian granulosa cells and follicular fluid was detected, and homeostatic model assessment of insulin resistance (HOMA-IR) and the levels of fasting plasma glucose (FPG), fasting insulin (FINS), and sex hormones were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(48 citation statements)
references
References 38 publications
4
44
0
Order By: Relevance
“…By the pre-ovulatory follicular stage, when the samples have been obtained, cumulus granulosa cells have differentiated from MGC and have significant dissimilarities in gene expression and post-transcriptional regulation patterns [ 27 , 66 ]. From EV samples hsa-miR-200c-3p [ 30 , 31 ], hsa-miR-17-5p [ 38 ] have been previously shown to be altered in PCOS women in line with the results of our study.…”
Section: Discussionsupporting
confidence: 90%
“…By the pre-ovulatory follicular stage, when the samples have been obtained, cumulus granulosa cells have differentiated from MGC and have significant dissimilarities in gene expression and post-transcriptional regulation patterns [ 27 , 66 ]. From EV samples hsa-miR-200c-3p [ 30 , 31 ], hsa-miR-17-5p [ 38 ] have been previously shown to be altered in PCOS women in line with the results of our study.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, PVT1 overexpression and miR-17-5p inhibition reversed these results. This study showed that both PVT1 downregulation and miR-17-5p up-regulation lead to PTEN inhibition, which promoting proliferation and repressing apoptosis of ovarian GCs in PCOS [54].…”
Section: Lncrna-pvt1mentioning
confidence: 74%
“…For example, the lncRNA NORFA inhibited granulosa cell apoptosis through regulating miR-126/transforming growth factor- β (TGF- β ) axis [ 12 ]. Knockdown of PVT1 promoted cell proliferation, as well as inhibition of apoptosis of ovarian granulosa cells by regulating miR-17-5p and PTEN [ 28 ]. The lncRNA HOTAIR aggravated the endocrine disorders and granulosa cell apoptosis through competitive binding to miR-130a to upregulate the expression of IGF1 [ 14 ].…”
Section: Discussionmentioning
confidence: 99%